Air and hydrogen supply systems and equipment for PEM fuel cells: a review. Issue 4 (16th March 2022) - Zhao, Yuanyang; Liu, Yunxia; Liu, Guangbin; Yang, Qichao; Li, Liansheng; Gao, Zhicheng
Summary: Air and hydrogen supply systems are key subsystems of polymer electrolyte membrane (PEM) fuel cell systems. This paper reviews the research on the gas (air and hydrogen) supply systems and equipment for PEM fuel cells. The scroll, screw, Roots, and centrifugal compressors are the major structures of compressors applied in the PEM fuel cells. Most studies and applications focus on air supply systems with centrifugal compressors. Four configurations of hydrogen supply systems are introduced, and characteristics of ejectors and hydrogen compressors are presented. The main technical developing directions for gas supply systems have been represented. The essential techniques involve the coupling of air compressors with PEM fuel cell systems, compressor and expander matching in the air supply system, integration of cooling and humidification in compressors, and energy utilization of high-pressure hydrogen gas.